Suggestive evidence of predisposing haplotype of leptin gene in obesity among Malays in Terengganu, Malaysia population - Wan Rohani, Wan Taib; Aryati, Ahmad; Amiratul Athirah, Shamsuddin (2017)
The prevalence of obesity and overweight has become the critical global threat which leads to metabolic risks and mortality. Leptin is a hormone that regulates the food intake as well as food expenditure that is encoded by Leptin gene. Besides, Leptin gene had been proved to play a pivotal role in obesity pathogenesis. This study was sought to determine the single and haplotype association of the Leptin gene polymorphisms (G2548A, H1328080 and A19G) with obesity among Malay in Terengganu, Malaysia. This cross-sectional study comprised of 249 participants (148 overweight/ obese and 101 normal BMI as control). The PCR-RFLP technique was performed to distinguish the genotypes for the three polymorphisms of Leptin gene. The allele and genotype frequencies were assessed for single and haplotype analyses. Single association analysis for G2548A, H1328080 and A19G polymorphisms of Leptin yielded no statistically significant association with obesity with the p-value of 0.74, 0.56 and 0.38 respectively. However, haplotype association analysis might suggest that haplotype AAG deliberated susceptibility with P=0.002, OR=8.897 (1.59–9.78) to obesity predisposition. This data on single and haplotype might disclose the preliminary exposure and pave the way for the obesity development with an evidence of revealed susceptibility to obesity.